2022
DOI: 10.3390/nu14091942
|View full text |Cite
|
Sign up to set email alerts
|

The Side-Effects of the COVID-19 Pandemic: Increased BMI z-Score in Children with Overweight and Obesity in a Personalised Lifestyle Intervention One Year after the Start of the Pandemic in The Netherlands

Abstract: Background: Early research showed weight gain in children during the COVID-19 pandemic. Objective: To compare changes in BMI z-score of children with overweight and obesity in a personalised lifestyle intervention before and during the pandemic. Methods: Changes in BMI z-score half a year (T6) and twelve months (T12) after the first lockdown were included for 71 children in the ‘2020 during COVID’ group and compared to 48 children in the ‘2019 before COVID’ group, using a marginal model for repeated measures (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 33 publications
0
10
1
4
Order By: Relevance
“…Whereas having a mother with obesity has been linked with reduced weight loss or with increasing BMIz in childhood in smaller studies [40,41], we observed parental overweight/obesity as a proxy that hampers pronounced BMIz loss.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…Whereas having a mother with obesity has been linked with reduced weight loss or with increasing BMIz in childhood in smaller studies [40,41], we observed parental overweight/obesity as a proxy that hampers pronounced BMIz loss.…”
Section: Discussioncontrasting
confidence: 68%
“…Patient and family adherence to behavioral recommendations is highly important for long-term outcome [45]. Moreover, the occurrence of COVID-19 was shown to negatively impact LI success [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quality was assessed using the modified Newcastle–Ottawa Scale [ 19 ]. Out of included forty studies, 16 were classified as good quality [ 26 , 27 , 33 38 , 45 , 46 , 48 , 49 , 54 , 58 , 59 ] while twenty-four were also classified as satisfied [ 21 25 , 28 31 , 39 44 , 47 , 50 53 , 55 – 57 , 60 ]. Twenty-four articles were done on the adult population [ 22 , 23 , 25 , 26 , 28 30 , 36 , 38 , 42 44 , 46 , 48 50 , 55 , 57 59 ], five articles were done only adolescents [ 31 , 39 , 41 , 47 , 60 ], three research articles were also done on children [ 34 , 53 , 54 ], and finally, eight articles were done on both children and adolescents [ 21 , 24 , 27 , 33 , 37 , 45 , 52 , 56 ] as shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…A history of COVID-19 infection leads to increased body weight [ 27 ]. Finally, missing consultations were reported as a risk factor for obesity during the COVID-19 pandemic [ 45 ]. As reported in Table 1 .…”
Section: Resultsmentioning
confidence: 99%